High plasma D-dimer and von Willebrand factor levels are associated with risk of upper gastrointestinal bleeding in patients with chronic coronary syndromes receiving long-term antiplatelet therapy. (14th October 2021) - Korobkova, V; Komarov, A L; Shakhmatova, O O; Dobrovolsky, A B; Novikova, E S; Guskova, E V; Titaeva, E V; Yarovaya, E B; Shuleshova, A G; Panchenko, E P
Abstract: Purpose: Plasma von Willebrand factor (VWF) and D-dimer levels have been proposed as markers of endothelial damage, coagulation activation and subsequent cardiovascular events. Thrombotic and hemorrhagic burdens are closely related. However, the association of coagulation markers with bleeding complications in pts with atherosclerosis remains unclear. We aimed to assess the predictive value of D-dimer and VWF levels for upper gastrointestinal bleeding (UGIB) in patients with chronic coronary syndromes (CCS) receiving long-term antithrombotic therapy. Patients and methods: Single center prospective Registry of Long-term AnTithrombotic TherApy (REGATTA-1 NCT04347200) included 934 pts with CCS (78.6% males, age 61±10.7 yrs, 76% after elective PCI). The UGIB annual incidence was 1.9 events per 100 patient-years. VWF was determined in 28 pts with UGIB and 141 controls, matched for age, sex and main clinical risk factors. D-dimer was determined from 28 and 380 pts respectively Results: The median for VWF was 139 [interquartile range 107–168]%. The median for D-dimer was 443, 8 [interquartile range 272.5–702.4] ng/ml. ROC analysis revealed acceptable discriminatory ability for VWF (cut off >105%; AUC=0.67, 95% CI: 0.59–0.74, p=0.001) and for D-dimer (cut off >928 ng/ml; AUC=0.63, 95% CI: 0.59–0.68, p=0.002). High levels of coagulation markers remained significant in regression model adjuster for ESC panel of UGIB risk factors. OR for D-dimer = 3.4, 95% CI: 1.09–10.66; p=0.03). OR for VWF = 11.74, 95% CI: 1.19–116.18; p=0.03). Conclusion: VWF and D-dimer should be considered as valuable prognostic biomarkers to improve the prediction of UGIB in addition to well-known scoring systems in CCS patients receiving long-term antithrombotic therapy. FUNDunding Acknowledgement: Type of funding sources: None.